The Role of Board Commissioner Size, Independent Commissioner, Ownership Concentration, Leverage, and Firm Size on Intellectual Capital Disclosure - Anis Maryanih; Lia Uzliawati; Agus Sholikhan Yulianto (Jurnal Riset Akuntansi Terpadu, 2023)
The purpose in this study to determinate the effect of board of commissioner size, independent commissioner, ownership concentration, leverage, and firm size to intellectual capital disclosure in banking sector listed on Indonesian Stock Exchange 2017-2020. This study used purposive sampling to sample selection and found 148 sample data. The data obtained from Indonesian Stock Exchange website. This study used data analytical method is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and goodness of fit models by SPSS version 25. This study find is board of commissioner size, independent commissioner, and ownership concentration have no effect on intellectual capital disclosure. Then, Leverage, and firm size have effect on intellectual capital disclosure